Inter-agency governance risk in managing hospital responses to extreme weather events in New South Wales, Australia: a facilities management perspective of shared situational awareness - Martin Loosemore; Vivien Chow; Tracie Harvison (2013)
Extreme weather is predicted to become more frequent and severe into the future. While our understanding of hospital infrastructure vulnerability to such events has advanced considerably in recent years, current approaches to healthcare facilities management treat hospitals in isolation from their surrounding governance infrastructure. However, recent research indicates that if hospital resilience is to be properly understood, health infrastructure must be managed holistically, as part of a much larger governance system of interdependent organizations. The inter-agency governance risks associated with this system are currently ignored in the facilities management literature. To explore these risks, an in-depth case study of 24 agencies in the state of New South Wales, Australia is presented. The results show that facilities managers are embedded in a highly complex and dynamic array of governance boundaries which are largely unresolved and misunderstood. A number of practical strategies are presented which could be adopted to significantly improve facilities manager’s integration into this system. These include: mapping hospital dependency on other agencies to build surge capacity; resolving overlapping operational boundaries with other agencies; proactive risk reduction for critical external support infrastructure; understanding potential conflicts with the objectives external agencies in responding to an extreme weather event.